2001
DOI: 10.1034/j.1600-0706.2001.950307.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and survival in parasitic wasps: sugar concentration and timing matter

Abstract: Siekmann, G., Tenhumberg, B. and Keller, M. A. 2001. Feeding and survival in parasitic wasps: sugar concentration and timing matter. -Oikos 95: 425-430.Sugar consumption can increase the longevity and lifetime fecundity of many species of parasitic wasps. Consequently, for these insects the availability of sugar sources in the field is important for their reproductive success. As sugar sources can be highly variable in quantity, space and time, the chances of finding a sufficient amount of sugar to increase lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
58
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 38 publications
4
58
1
Order By: Relevance
“…However, feeding time on a sugar solution may not always reflect consumption of the solution because of different feeding speeds due to different viscosities of the sugars (Siekmann et al, 2001;Wäckers, 2001;Wäckers et al, 2006;Faria et al, 2008;Wyckhuys et al, 2008). In the present study, we found positive linear relationships between feeding time and consumption for 1 mol l −1 in all four sugars, suggesting that at this concentration, feeding time is a good indicator of gustatory responses and consumption in all sugars tested.…”
Section: Relationship Between Sugar Feeding Time and Consumptionsupporting
confidence: 44%
See 1 more Smart Citation
“…However, feeding time on a sugar solution may not always reflect consumption of the solution because of different feeding speeds due to different viscosities of the sugars (Siekmann et al, 2001;Wäckers, 2001;Wäckers et al, 2006;Faria et al, 2008;Wyckhuys et al, 2008). In the present study, we found positive linear relationships between feeding time and consumption for 1 mol l −1 in all four sugars, suggesting that at this concentration, feeding time is a good indicator of gustatory responses and consumption in all sugars tested.…”
Section: Relationship Between Sugar Feeding Time and Consumptionsupporting
confidence: 44%
“…This suggests that feeding speed is lower for maltose solutions than for the other sugar solutions. Siekmann et al (Siekmann et al, 2001) and Wyckhuys et al (Wyckhuys et al, 2008) suggest that the higher viscosity of maltose may reduce feeding speed relative to the other sugars, but Nithiyanantham and Palaniappan (Nithiyanantham and Palaniappan, 2013) and Chirife and Buera (Chirife and Buera, 1997) …”
Section: Relationship Between Sugar Feeding Time and Consumptionmentioning
confidence: 99%
“…Previous laboratory studies show that adult parasitoids deprived of access to nectar or sugar sources have a reduced longevity and/or fecundity (Jacob & Evans, 2000;Schmale et al, 2001;Siekmann et al, 2001). The energy obtained through adult feeding on supplemental sugar sources may also be necessary for sustaining flight capacity in parasitoids because flight in insects is a highly energy-demanding behaviour with metabolic rates during flight increasing 50-100-fold compared with metabolism at rest (Beenakkers et al, 1984;Hoferer et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the field, adult parasitoids are observed visiting flowering plants to feed on floral or extrafloral nectar (Jervis et al, 1993;Idris & Grafius, 1995), and crops with nearby flowering vegetation have higher parasitism rates (Landis & Hass, 1992;Zhao et al, 1992;Stephens et al, 1998), although the finding of a recent field study suggests that vegetative characteristics of floral resource plants rather than flowers might influence the abundance of natural enemies (Rebek et al, 2005). In the laboratory, plant nectar shows a higher nutritional value compared with honeydew for sustaining longevity and fecundity in hymenopteran parasitoids (McDougall & Mills, 1997;Wa¨ckers, 2002;Lee et al, 2004).Previous laboratory studies show that adult parasitoids deprived of access to nectar or sugar sources have a reduced longevity and/or fecundity (Jacob & Evans, 2000;Schmale et al, 2001;Siekmann et al, 2001). The energy obtained through adult feeding on supplemental sugar sources may also be necessary for sustaining flight capacity in parasitoids because flight in insects is a highly energy-demanding behaviour with metabolic rates during flight increasing 50-100-fold compared with metabolism at rest (Beenakkers et al, 1984;Hoferer et al, 2000).…”
mentioning
confidence: 99%
“…Sugar feeding has been reported to increase parasitoids longevity (Wäckers, 2001; Siekmann et al, 2001) as well as its fecundity (Schmale et al, 2001). In addition, well fed parasitoids are usually more active and more focused in seeking out their herbivores hosts (Wäckers, 1994).…”
Section: Introductionmentioning
confidence: 99%